Mitophagy and Innate Immunity in Infection - Cho, Dong-Hyung (Mol Cells, 2020)
Mitochondria have several quality control mechanisms by which they maintain cellular homeostasis and ensure that the molecular machinery is protected from stress. Mitophagy, selective autophagy of mitochondria, promotes mitochondrial quality control by inducing clearance of damaged mitochondria via the autophagic machinery. Accumulating evidence suggests that mitophagy is modulated by various microbial components in an attempt to affect the innate immune response to infection. In addition, mitophagy plays a key role in the regulation of inflammatory signaling, and mitochondrial danger signals such as mitochondrial DNA translocated into the cytosol can lead to exaggerated inflammatory responses. In this review, we present current knowledge on the functional aspects of mitophagy and its crosstalk with innate immune signaling during infection. A deeper understanding of the role of mitophagy could facilitate the development of more effective therapeutic strategies against various infections.